Fiscal redistribution, poverty, and inequality in Botswana - Taylor, Lotte (School of Economics, 2024)
With mineral revenues forecast to diminish, Botswana's state-funded public services and social protection give the government cause for efficiency concerns in its pursuit of "achieving shared prosperity for all". Meanwhile data-driven policies are impeded by divergent estimated levels and trends for poverty and inequality. The objective of this study is to develop a welfare measure for Botswana which allows for providing internally consistent estimates for the impact of its fiscal instruments on welfare, poverty, and inequality. Using the most recent household surveys, data and measurement challenges are evaluated applying established national and international measures. The research expands on related studies for Botswana and contributes to the internationally comparable fiscal incidence literature using the CEQ methodology. Results reveal that the official (2015/16) poverty headcount measures are underestimated, while poverty and inequality trends are ambiguous and dependent on the unit of analysis. Accounting for welfare from housing consumption (paid and imputed rents) changes the poverty profile and lowers estimated inequality. Estimated marginal redistributive and poverty reducing contributions for each fiscal instrument provide tools for evaluating recent and potential future policy options through static simulations. At the international extreme poverty line, fiscal redistribution via direct transfers reduces poverty by half (from 19.2% to 9.6E%), only marginally counter-balanced by the poverty-increasing combined impact of indirect taxes and subsidies (increasing the headcount to 10.7%). The many small schemes and some universal schemes provide wide overall coverage with free school meals, the Ipelegeng public works scheme, and the universal old age pension having the largest marginal contributions to reducing extreme poverty. Parsimonious benefits leave a large share of the population still poor considering Botswana's status as upper-middle income country. Making up a similar share of total pre-fiscal income, the direct transfers have a larger redistributive effect than personal income tax, reducing inequality by 3.0 and 2.4 Gini points, respectively. To improve monitoring and policy-response to developments in poverty and inequality, adjustments and corrections are proposed for updating the welfare and poverty concepts and for addressing data quality concerns and measurement bias.